2007
DOI: 10.1128/aac.00999-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Streptococcus mutans Biofilm Formation on Hydroxyapatite by Subinhibitory Concentrations of Anthraquinones

Abstract: We report that certain anthraquinones (AQs) reduce Streptococcus mutans biofilm formation on hydroxyapatite at concentrations below the MIC. Although AQs are known to generate reactive oxygen species, the latter do not underlie the observed effect. Our results suggest that AQs inhibit S. mutans biofilm formation by causing membrane perturbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Dental plaque is caused by biofilm formation of microorganisms on the tooth surface which exhibits several properties including reduced susceptibility to antibacterial agents (Loesohe, 1986). S. mutans was classified as the primary bacteria causing dental plaque so that prevention of biofilm formation by S. mutans could reduce the incidence of tooth decay and periodontal diseases (Coenye et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Dental plaque is caused by biofilm formation of microorganisms on the tooth surface which exhibits several properties including reduced susceptibility to antibacterial agents (Loesohe, 1986). S. mutans was classified as the primary bacteria causing dental plaque so that prevention of biofilm formation by S. mutans could reduce the incidence of tooth decay and periodontal diseases (Coenye et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Natural products and derivatives, such as green tea catechins (Hirasawa et al 2006), cranberry constituents , Galla chinensis (Xie et al 2008), citrus lemon oil (Liu et al 2013), mushroom extracts (Yano et al 2010), and several bioactive macromolecules (Shang et al 2014;Lee and Park 2015), have been reported to be effective against the growth and adherence of S. mutans. In addition, small molecules, such as tt-farnesol (Koo et al 2003), walkmycin C (Eguchi et al 2011), and anthraquinones (Coenye et al 2007), have been shown to inhibit the growth of cariogenic bacteria, and even the development of caries, but few of these compounds target S. mutans biofilms. Therefore, there is an urgent need to identify new approaches capable of targeting cariogenic bacteria in the biofilm state.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The TC content in the films was optimum for antimicrobial activity. It is known that the MIC of the TC against Streptococcus mutans is 16 μg/ml (19). The normal saliva volume is 0.7 ml (20).…”
Section: Determination Of Tc Contentmentioning
confidence: 99%